+0  
 
0
170
1
avatar+4269 

Help.

NotSoSmart  Feb 2, 2018
 #1
avatar+7339 
+2

1.

 

f(x) + g(x)

                                                   Since  f(x)  =  -5x - 4, we can substitute  -5x - 4  in for  f(x)

f(x) + g(x)  =  (-5x - 4) + g(x)

                                                   Since  g(x)  =  6x - 7, we can substitute  6x - 7  in for  g(x)

f(x) + g(x)  =  (-5x - 4) + (6x - 7)

 

f(x) + g(x)  =  -5x - 4 + 6x - 7

                                                   Combine like terms.

f(x) + g(x)  =  x - 11

 

2.

 

f(x) - g(x)

                                                   Since  f(x)  =  3x + 2, we can substitute  3x + 2  in for  f(x)

f(x) - g(x)  =  (3x + 2) - g(x)

                                                   Since  g(x)  =  6x - 7, we can substitute  6x - 7  in for  g(x)

f(x) - g(x)  =  (3x + 2) - (6x - 7)

                                                   Distribute the  -1  to the terms in parenthesees.

f(x) - g(x)  =  3x + 2 - 6x + 7

                                                   Combine like terms.

f(x) - g(x)  =  -3x + 9

hectictar  Feb 2, 2018

34 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.